Importance of Clinical Decision Making by Experienced Pediatric Surgeons When Children Are Suspected of Having Acute Appendicitis: The Reality in a High-Volume Pediatric Emergency Department. Issue 9 (September 2017) - Bal, Alkan; Anil, Murat; Nartürk, Müge; Özdemir, Tunç; Arikan, Ahmet; Köylüoğlu, Gökhan; Polat, Burak; Erdoğan, Nuri; Bayol, Umit; Özgüzer, Alp; Çolak, Ayfer
Abstract : Objective: The aim of the present study was to compare the pediatric appendicitis score (PAS), the Alvarado score (AS), white blood cell count (WBC), absolute neutrophil count (ANC), C-reactive protein (CRP) level, procalcitonin level, and ultrasound (US) data, with the appendectomy decisions of pediatric surgeons diagnosing acute appendicitis (AA) in a real-life setting; this was a top-level, high-volume pediatric emergency department (PED) in a developing country. Methods: The study was conducted prospectively between January 2012 and June 2013 in the PED of the Tepecik Teaching and Research Hospital in Izmir, Turkey. The study was observational in nature; no attempt was made to influence indications for exploration or the timing thereof. Children aged 4 to 18 years presenting to the PED on suspicion of AA were included. The WBC, ANC, CRP level, and procalcitonin level were measured, and US was performed on all patients on admission. The PAS and AS were calculated. An operative decision was made by each pediatric surgeon who had the results of laboratory and radiological tests. The criterion standard for AA was histopathological assessment. Results: Upon receiver operating curve (ROC) analysis, the areas under the ROCs (AUROCs) of the WBC, ANC, CRP level, procalcitonin level, US positivity, PAS, AS, and decisions of pediatric surgeons supported by laboratory and US data were 0.734, 0.741, 0.671, 0.675, 0.670, 0.831, 0.794, and 0.910, respectively. When US data were employed only in cases with PASs 4 to 7, the sensitivity increased but specificity decreased. The sensitivity and specificity of pediatric surgical decisions were 100% and 82.50%, respectively. The difference between the PAS AUROC and the pediatric surgeon decision-making AUROC was significant ( P = 0.0393; 95% confidence interval, 0.0470–0.226). Conclusions: Good pediatric surgical decision making supported by laboratory and US data for those suspected of AA may be the most effective diagnostic tool in a high-volume PED in a developing country.